2007
DOI: 10.1080/14622200701188893
|View full text |Cite
|
Sign up to set email alerts
|

Effects of smoking abstinence and alcohol consumption on smoking-related outcome expectancies in heavy smokers and tobacco chippers

Abstract: Smoking cessation interventions often target expectancies about the consequences of smoking. Yet little is known about the way smoking-related expectancies vary across different contexts. Two internal contexts that are often linked with smoking relapse are states associated with smoking abstinence and alcohol consumption. This report presents a secondary analysis of data from two experiments designed to examine the influence of smoking abstinence, and smoking abstinence combined with alcohol consumption, on sm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(51 citation statements)
references
References 42 publications
2
48
1
Order By: Relevance
“…Kirchner and Sayette (2007) proposed a different direction of association in which the effect of alcohol consumption on smoking outcome expectancies is mediated by smoking urge. However, the current study failed to find a significant effect of alcohol consumption before time j and positive outcome expectancies at time j +1.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kirchner and Sayette (2007) proposed a different direction of association in which the effect of alcohol consumption on smoking outcome expectancies is mediated by smoking urge. However, the current study failed to find a significant effect of alcohol consumption before time j and positive outcome expectancies at time j +1.…”
Section: Discussionmentioning
confidence: 99%
“…Laboratory studies have found that, relative to placebo, alcohol consumption significantly increased the intensity of smoking urges in moderate to heavy drinkers (Burton & Tiffany, 1997; King, McNamara, Conrad, & Cao, 2009) as well as in chippers (Epstein, Sher, Young, & King, 2007; Sayette, Martin, Wertz, Perrott, & Peters, 2005), light smokers (King & Epstein, 2005), heavy smokers (Sayette et al, 2005), and abstaining smokers (Kirchner & Sayette, 2007). Furthermore, a positive dose-response relationship was found between alcohol consumption and urge to smoke (King & Epstein, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…According to a recent analysis, two internal contexts that are often linked with smoking relapse are states associated with smoking abstinence and alcohol consumption (Kirchner and Sayette 2007). This work presented secondary analysis of data from two experiments designed to examine the influence of smoking abstinence and smoking abstinence combined with alcohol consumption, on smoking-related outcome expectancies among heavy smokers and tobacco chippers.…”
Section: Alcohol Consumption and Binge Drinkingmentioning
confidence: 99%
“…Among smokers, the most frequently endorsed smoking outcome expectancy is that smoking will alleviate negative affect (Brandon & Baker, 1991), and some evidence suggests that positive smoking outcomes expectancies may be triggered and increase as a function of internal states such as negative affect (Baker et al, 2004; Gwaltney, Shiffman, Paty, & Balabanis, 2005; Kirchner & Sayetter, 2007). …”
Section: Associations Among Affect Outcome Expectancies and Urgementioning
confidence: 99%